2018
DOI: 10.1016/j.jalz.2018.06.666
|View full text |Cite
|
Sign up to set email alerts
|

P1‐654: Comparison of Pharmacologic and Non‐pharmacologic Interventions in People With Alzheimer's Disease and Related Disorders

Abstract: Background: Although recent studies have shown that multimodal intervention has positive effects on cognition, little is known about how frequent intervention should be held to keep their cognition for mild cognitive impairment (MCI). The purpose of this study was to investigate the relationship between the participation rate in a multimodal day-care program and longitudinal cognitive outcome in MCI patients. Methods: Sixty-three patients with MCI (28 female), aged 54-83 years (70.7 6 6.6 years) participated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The complexity of BPSD is a contributing factor to fragmented patient care resulting in a poorer prognosis, accelerated cognitive decline, illness progression and prolonged institutionalization (Anderson et al, 2020; Wolverson et al, 2019). The pharmacological interventions identified in the literature emphasized the use of antipsychotics and antidepressants to minimize the symptoms of BPSD (Dannenbaum et al, 2018; Mishriky & Reyad, 2018) used by the multidisciplinary team (Cohen‐Mansfield, 2018; Sutherland, 2018). Current systematic and literature reviews have identified evidence‐based nonpharmacological interventions to manage BPSD, including aromatherapy, pet therapy, environmental modification, sensory modulation and so on.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The complexity of BPSD is a contributing factor to fragmented patient care resulting in a poorer prognosis, accelerated cognitive decline, illness progression and prolonged institutionalization (Anderson et al, 2020; Wolverson et al, 2019). The pharmacological interventions identified in the literature emphasized the use of antipsychotics and antidepressants to minimize the symptoms of BPSD (Dannenbaum et al, 2018; Mishriky & Reyad, 2018) used by the multidisciplinary team (Cohen‐Mansfield, 2018; Sutherland, 2018). Current systematic and literature reviews have identified evidence‐based nonpharmacological interventions to manage BPSD, including aromatherapy, pet therapy, environmental modification, sensory modulation and so on.…”
Section: Introductionmentioning
confidence: 99%
“…In acute and subacute hospital settings, the therapeutic approaches to managing BPSD in patients with dementia vary because of the multifactorial and complex symptomology (Bailey et al, 2017; Brodaty et al, 2018). Management of BPSD includes both pharmacological and nonpharmacological interventions (Caspar et al, 2018; Dannenbaum et al, 2018; Kishita et al, 2020). Historically, pharmacological interventions have been commonly used by health care professionals to manage the complexity of BPSD (Kales et al, 2019; Nemlekar & Srivastava, 2020).…”
Section: Introductionmentioning
confidence: 99%